Synthesis and characterization of photocatalyst nanocomposite for the degradation of organic pollutants in wastewater - Faridah Lisa Supian (Tanjung Malim, 2023)
Synthesis and characterization of photocatalyst nanocomposite for the degradation of organic pollutants in wastewater by Faridah Lisa Supian